MASJID SEBAGAI PUSAT PENDIDIKAN AGAMA ISLAM - Muhammad Rifai (Pusat Studi Pendidikan dan Kreatifitas Anak Purwokerto, 2020)
One of the places to pray for the Muslims is a mosque although in fact, in Islamic law the whole earth can be used to perform prayer, except in places where there is a prohibition to perform prayer in it.as the word of the Messenger of Allaah 'alaihi Wasallam which means: